PENCEMARAN AIR DAN DAMPAKNYA TERHADAP DUNIA PERIKANAN - Susatyo Adhi Pramono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2008)
AbstractHuman with the environments shall can run adjoining. Development is one of human effort to be able increase the life prosperity, but development do not mean must disregard environmental ability in sustaining it. Environmental pollution as product from development will affect again human as development agent.Keyword: Development, environmental pollution, human.